The relative age effect has no influence on match outcome in youth soccer - Kirkendall, D. T. (Journal of Sport and Health Science, 2014)
Purpose: In age-restricted youth sport, the over-selection of athletes born in the first quarter of the year and under-selection of athletes born in the last quarter of the year has been called the relative age effect (RAE). Its existence in youth sports like soccer is well established. Why it occurs has not been identified, however, one thought is that older players, generally taller and heavier, are thought to improve the team's chances of winning. To test this assumption, birth dates and match outcome were correlated to see if teams with the oldest mean age had a systematic advantage against teams with younger mean ages. Methods: Player birth dates and team records (n = 5943 players on 371 teams; both genders; U11-U16) were obtained from the North Carolina Youth Soccer Association for the highest level of statewide youth competition. Results: The presence of an RAE was demonstrated with significant oversampling from players born in the 1st vs. the 4th quarter (overall: 29.6% vs. 20.9% respectively, p < 0.0001). Mean team age was regressed on match outcomes (winning %, points/match, points/goal, and goals for, against, and goal difference), but there was no evidence of any systematic influence of mean team age and match outcomes, except possibly in U11 males. Conclusion: Selecting players based on physical maturity (and subsequently, on age) does not appear to have any systematic influence on match outcome or season record in youth soccer suggesting that the selection process should be focused on player ability and not on physical maturation